EXPLORING THE SPATIALIZATION OF CULTURE: PERSPECTIVES FROM SLOVENIAN ETHNOLOGY - Ingrid Slavec Gradišnik (Zbornik Radova: Geografski institut "Jovan Cvijić")
The article presents observations on the intricate processes of localizing peoples and cultures, drawing on their spatial mapping, a practice known since antiquity. The introducing part outlines general views on the causal relationship between culture and environment. The Enlightenment put forward the hypothesis of environmental determinism, which provided a rationale for linking people, cultures, and geographies well into the 20th century, particularly in anthropogeography and culture-area research. The isomorphism of space/place and culture characterized research until the late 20th century when the postmodern turns called it into question. The theory of practice and the spatial turn proved particularly influential in anthropology and ethnology. In this field, the central concept of culture has been deconstructed; this has stimulated debates about ethnography as a genre of “writing culture” and fieldwork as a locally grounded research practice. The second part of the text shows how Slovenian ethnology in the 20th century pursued cultural area research shared with other European regional or national ethnologies that focus on the national territory. However, research has not shown a clear correspondence between cultural and ethnic/national boundaries. In this respect, ethnology has maintained a critical distance from cultural essentialization. On the other hand, it has not particularly reflected upon space; space has functioned as the natural environment, the obvious background of culture. In this respect, the reception of the spatial turn brought a particular sensitivity to studying spatial practices and experiences and refining research methodologies.